Peran Audit Internal Pada Efektivitas Pengendalian Internal Mendukung Kredit Investasi Di Cabang BRI Di Situbondo - Rachmawati, Ratih (Relasi : Jurnal Ekonomi, 2018)
Purpose of this research is to obtain a picture of the effectiveness of intenal audit and how the role of internal audit in supporting the effectiveness of the investment credit control.The method used in this research is descriptive analysis method, where data obtained by the author analyzed and compared with some existing theories. Based on the results of the research authors conclude that the overall implementation of internal audit in the branch branch Bank Rakyat Indonesia in Situbondo for credit monitoring activities have been adequate for investment in accordance with the rules and policies set by the central office, but it also includes compliance, verivication and evaluation. Thus, these findings have been in accordance with the propositions that have been made in the implementation of the study conducted internal audits can adequately support the achievement of the effectiveness of internal control in the process of granting investment credits the branch branch Bank Rakyat Indonesia in Situbondo Keywords : Internal Audit role, Internal control system, Investment credit